Acceptance Test of Donuts Made From Moringa Leaf Flour ( Moringa oleifera L ) and Ruku's Leaf Flour ( Ocimum americanum L ) - Indah Indah; Cut Shaviatul Bayti; Hamibah Mini; Yayi Retno Pangestu W; Adi Bejo Suwardi (Jurusan Gizi Poltekkes Kemenkes Makassar, 2020)
Donuts become one of the food products that are widely known by the public. Donuts are in demand by the public and now many variants have been found in the market. Fortified of M. Oleifera, O. As food additives, Americanum leaves can forced to offer additional nutritional value in donuts. The purpose of the study is to find out the test of the thank-power doughnut that is fortified with kelor leaf flour and my ruku-leaf flour. This study aims to determine product preferences for fortified donut products with Moringa oleifera L. Flour and leafy ruku-ruku (Ocimum americanum L.). This method of research used in this study was an experiment using a fully randomized two-component research design, namely: moringa leaf flour with ruku leaves- 2 treatments, namely A1 with a comparison of moringa leaf flour, Ruku-ruku leaf flour 6%: 10%: 84% and A2 with the ratio of moringa leaf flour, Ruku-ruku leaf flour 6%: 10%: 84%. The result data is grouped and then processed using the Microsoft Excel program and the resultant organoleptic test data in the form of a 20-person acceptance test (hedonic test). The results showed the reasonableness level in the form of different tastes, aromas, colors, and textures. Panelists are more interested in donut food preferences and colors. Organoleptic testing for panelists is obtained that donut A products are the most widely accepted by panelists with a total acceptance of 11.3.